Reading McDowell : on Mind and world - Smith, Nicholas H. (Nicholas Hugh), 1962- (Routledge, 2002)
Internationally renowned contributors analyse and discuss John McDowell's challenging Mind and World. Concludes with responses from McDowell himself. An important contribution to analytic philosophy and the broader philosophical debate.